Pleasure principle and perfect happiness: morality in Jacques Lacan and Zhuangzi. - Wang, Quan (Asian Philosophy, 2018)
Jacques Lacan studied Chinese classics and received much inspiration from Zhuangzi. This paper concentrates on the comparative study of morality in those two thinkers from three connecting levels, namely, nature as the source of ethical codes, reason as the means to arrive at the ethical state, and pleasure as the ultimate purpose of morality. The investigation into the topic is enlightening for posthuman morality. Zhuangzi’s idea of the poetics of oneness inspires the Lacanian concept of the Real and ushers us into a new territory to rethink animal rights.